PENETAPAN KADAR TANIN EKSTRAK ETANOL DAUN KETEPENG CINA (Cassia alata L.) SECARA SPEKTROFOTOMETRI UV-VIS TAHUN 2022 - Julike, Katarina; Sari Br Bangun, Sofia Elia; ., Sulasmi; charisa, Jilli; Fitria Anggraini, Tengku Dinda (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
In general, people use plant parts which include roots, bark, leaves, flowers or seeds as medicinal ingredients. Chinese ketepeng (Cassia alata L.) is one of the plants that is often used by the community as traditional medicine. This Chinese ketepeng plant is known as the wax tree, wax bush and ringworm plant. Chinese ketepeng leaf is one part that is often used by the community to treat skin infections caused by fungi, such as tinea versicolor, ringworm, thrush, water fleas and others. Tannins are organic compounds that are very complex and consist of phenolic compounds found in various plants. Tannins are considered as a group of compounds that attract applications in terms of potency and environmental prediction. The analytical method used is qualitative using FeCl3 reagent, gelatin and Folin Ciocalteu, while quantitative testing is using UV-Vis spectrophotometry with a wavelength of 725 nm with gallic acid as a comparison raw material. The results of the qualitative analysis of the positive samples contained tannins. The quantitative results of the ethanol extract of Chinese ketepeng leaves were 8.71 mg/g. Based on the results of research that has been carried out, tannin compounds in the ethanol extract of the leaves of the Chinese Ketepeng (Cassia Alata L.) can be determined using UV-Vis spectrophotometry using gallic acid as a standard.